Research on Operation Optimization of Energy Cascade Utilization Heating Based on Exergy Analysis - Jianjun HOU; Xiliang FU; Ransheng LI; Guixi LIU; Yanping SUN; Li SUN; Zhanwei LIANG (Zhongguo dianli)
In order to realize the optimization of energy cascade heating unit, An analysis-based evaluation model of heating economy is established, Got the whole plant efficiency, the heating index, And power generation coal consumption and heating coal consumption based on analysis; The simulation model built based on the thermal system integration and optimization software, This paper studies the operation economy of high back pressure heating unit, high and low side steam extraction-back pressure heating, middle exhaust steam heating and middle exhaust steam extraction-back pressure heating, The results show that the best efficiency, index, power generation coal consumption and heating coal consumption index of middle exhaust steam-back compressor are better than other heating modes; Based on the analysis method, the heating coal consumption can be the economy of different energy heating modes. The research results provide support for the operation optimization of energy cascade using heating transformer condition.